2017
DOI: 10.3390/su9020174
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Monitoring the Akagera Wetland in Rwanda

Abstract: Wetland maps are a prerequisite for wetland development planning, protection, and restoration. The present study aimed at mapping and monitoring Rwanda's Akagera Complex Wetland by means of remote sensing and geographic information systems (GIS). Landsat data, spanning from 1987 to 2015, were acquired from different sensor instruments, considering a 5-year interval during the dry season and the shuttle radar topographic mission (SRTM) digital elevation model (30-m resolution) was used to delineate the wetland.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Due to urbanization and its impact on land-use, several studies here have also examined land-use and land-cover changes (e.g., [1,2]) through mapping. So, urban environments are increasingly being addressed by physical geographers, as for instance geomorphologists as part of urban geomorphology [13,14] or what has been a growing "human geomorphology" (e.g., [15]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to urbanization and its impact on land-use, several studies here have also examined land-use and land-cover changes (e.g., [1,2]) through mapping. So, urban environments are increasingly being addressed by physical geographers, as for instance geomorphologists as part of urban geomorphology [13,14] or what has been a growing "human geomorphology" (e.g., [15]).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of methodological approaches are incorporated here, with spatial technology (remote sensing, GIS, etc.) included in several studies (e.g., [1][2][3][4]), serving to portray the role of technology on data compilation and analysis in geographical research. Data visualization is evident in paper [11] for modelling and, earlier in the Special Issue, [1] explores data-sharing based on data acquired from Earth observation.…”
Section: Discussionmentioning
confidence: 99%
“…For the objective of developing coherent and adoptable methods towards wetland mapping, we therefore valued the accessibility and availability of the SRTM DEM, substantiated with a large body of literature successfully using it for large-scale wetland mapping (e.g. Bwangoy et al 2010;Ndayisaba et al 2017;Ludwig et al 2019) over the higher performance of the TanDEM-X DEM.…”
Section: Wetland Delineationmentioning
confidence: 99%
“…5). The studies investigating threats to the Akagera Wetland from 1987 to 2015 showed water hyacinth to be the main problem, particularly in the 2000-2002 period (Twongo et al 2002;Ndayisaba et al 2017). However, these studies did not quantify the coverage of water hyacinth in the wetland during this period.…”
Section: Change Detectionmentioning
confidence: 99%